Pengaruh Tarif Perdagangan, Nilai Tukar dan Produk Domestik Bruto Terhadap Ekspor Produk Pertanian Indonesia Ke 5 Negara Asean dalam Prespektif Ekonomi Islam Tahun 2015-2024 - Karina Setiani; Sania Nuraziza; Erlin Kurniati (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
Agricultural product exports are closely related to trade tariffs, exchange rates, and gross domestic product. This study aims to analyze the influence of trade tariffs, exchange rates, and gross domestic product on agricultural product exports to ASEAN countries from an Islamic economic perspective. The research method used in this study is quantitative, presented in the form of panel data from five ASEAN member countries with a purposive sampling technique in data selection. The results of this study indicate that the trade tariff variable has a negative and significant effect on Indonesian agricultural exports, the exchange rate variable has a negative and significant effect on Indonesian agricultural product exports, and the GDP variable has a positive and significant effect on Indonesian agricultural product exports. In Islamic economics, exports and international trade must be in accordance with sharia, emphasizing halal (permissible), justice, and blessings. Goods or services traded must be halal (permissible), beneficial, and not detrimental to society or the environment. Trade contracts must be transparent, free from usury, gharar (unlawful), and fraud, while sharf (sharf) is carried out in cash and clearly. Trade tariffs are permitted to protect domestic interests fairly. The Islamic economic approach assesses economic activity from the perspective of its benefits, blessings, and suitability to the maqashid al-shariah, not just GDP.